Gender representation in children’s literature: Limits and potential in Stephen Alumenda’s Marita goes to school and Marita’s great idea, and Jairos Kangira’s The bundle of firewood (Journal for Studies in Humanities and Social Sciences, 2016)
Different societies across the globe usually contrast masculinity with femininity. Men are often por-trayed in more positive terms that include being strong, achievers and providers, while women are depicted as the opposite. Such masculinities have emerged to be frameworks within which literary texts can be critiqued. In this article, I employ hegemonic and subordinate masculinities to argue that children’s stories can be utilised to transform unequal gender relations. I explore how Stephen Alu-menda and Jairos Kangira respond to gender issues in Zimbabwean children’s literature. The first sec-tion is a brief introduction that unpacks the concept of children’s literature and places the discussion of gender representation in children’s literature within the context of African literature. In the second segment, I outline how Alumenda endeavours to promote the education of the girl child. The third part highlights how this theme is advanced by Jairos Kangira, another author of children’s books.